Workplace wellbeing among health care workers providing HIV services in primary care in Johannesburg: a mixed methods study - Ndinda Makina-Zimalirana; Melanie Bisnauth; Nosipho Shangase; Natasha Davies; Anele Jiyane; Fezile Buthelezi; Kate Rees; Kate Rees (Frontiers Media S.A., 2023)
BackgroundBurnout among Health Care workers (HCWs) impacts on provider-patient relations and quality of care. Anova Health Institute (Anova) is a large South African non-profit organization and PEPFAR/USAID implementing partner. We conducted a study among HCWs providing HIV-related services in primary care settings in Johannesburg, South Africa, to examine levels of burnout, understand factors affecting workplace wellbeing, and explore strategies to prevent burnout.MethodsWe used a sequential mixed-method approach. Data were collected between February and April 2022. The first phase consisted of a survey using the Maslach Burnout Inventory Human Services Survey (MBI-HSS) to measure levels of burnout. We then interviewed a subset of survey participants to understand the experiences that may affect wellbeing. We used descriptive statistics to quantify burnout rates for each MBI dimension (emotional exhaustion, personal accomplishment, and depersonalization). Qualitative data analysis was guided by the Job Demands-Resources Framework that explores the interactions between demands and resources in the workplace.ResultsSurvey findings (n = 194) revealed that although depersonalization rates were low at 6%, 21% of participants had high emotional exhaustion and 24% reported low professional accomplishment. Less than half (41%, n = 80) had scores in the high category for any one of the three MBI-HSS dimensions. The MBI-HSS dimensions differed significantly by type of work and job title. Roving positions (HCW working in more than one health facility) were more likely to experience higher emotional exhaustion and lower professional accomplishment. Qualitative findings (n = 25) indicate that a number of job demands, including high workload, inadequate mental health support, and challenging relationships with stakeholders, had a negative effect on HCWs' wellbeing. However, finding meaningfulness in their work, working as a team, and practicing autonomy were experienced as resources that reduced the negative effect of these demands.ConclusionWhile measured burnout syndrome rates were low, various experiences negatively impacted at least one in five HCW. We identified key resources that provided buffering against workplace stressors. We recommend that as well as addressing key drivers of burnout, access to these resources should be fostered, for example by strengthening interventions that offer recognition, and promoting team interactions through social activities and support groups.